Strategy to Strengthen the Halal Slaughterhouse Industry in Indonesia - Sri Mulatsih; Supratikno Supratikno; Ach Firman Wahyudi (Department of Islamic Economics, IPB University, 2025)
There are three types of slaughterhouse management in Indonesia, namely: by the government, individuals and the private sector, each with different management standards. This research aims to analyze strategies for strengthening halal slaughterhouses. The analysis method uses Analytical Hierarchy Process (AHP) and Important Performance Analysis (IPA) from expert judgment data representing bureaucrats, academics and practitioner. The results of the AHP show that the priority strategy for strengthening the halal slaughterhouse industry is certification for slaughterhouses and meat retailers as well as training for halal slaughterhouses and human resources. Halal performance attributes that are prioritized be improved by the three slaughterhouse managements are hygienic carcass cutting process and the presence of halal supervisors.